The formation, occurrence, and function of β-apocarotenoids: β-carotene metabolites that may modulate nuclear receptor signaling(1)(2)(3)(4) - Harrison, Earl H (American Society for Nutrition, 2012)
β-Carotene is the major dietary source of provitamin A. Central cleavage of β-carotene yields 2 molecules of retinal followed by further oxidation to retinoic acid. Eccentric cleavage of β-carotene occurs at double bonds other than the central double bond, and the products of these reactions are β-apocarotenals and β-apocarotenones. We reviewed recent developments in 3 areas: 1): the enzymatic production of β-apocarotenoids in higher animals; 2) the occurrence of β-apocarotenoids in foods and animal tissues; and 3) the biological activity of β-apocarotenoids, particularly on retinoid receptors. HPLC–mass spectrometry techniques were developed to quantify these compounds in mouse serum and tissues and in foods. β-Apo-10′- and -12′-carotenals were detected in mouse serum and liver. β-Apo-8′-, β-apo-10′-, β-apo-12′-, and β-apo-14′-carotenals and β-apo-13-carotenone were detected in orange-fleshed melons. Transactivation assays were performed to see whether apocarotenoids activate or antagonize retinoid X receptor (RXR) α. Reporter gene constructs and retinoid receptor (RXRα) were transfected into cells, which were used to perform quantitative assays for the activation of this ligand-dependent transcription factor. None of the β-apocarotenoids significantly activated RXRα. However, β-apo-13-carotenone antagonized the 9-cis-retinoic acid activation of RXRα. Competitive radioligand binding assays showed that this antagonist competes directly with the agonist for binding to purified receptor, a finding confirmed by molecular modeling studies. These findings suggest that a possible biological function of β-apocarotenoids is their ability to interfere with nuclear receptor signaling. Recent work showed that β-apo-13-carotenone is also a high-affinity antagonist of all 3 retinoic acid receptors (RARα, RARβ, and RARγ).